2020
DOI: 10.1021/acssuschemeng.0c03877
|View full text |Cite
|
Sign up to set email alerts
|

Surface Morphology and Chemical Mapping of UV-Aged Thin Films of Bitumen

Abstract: This study decouples effects of ultraviolet (UV) exposure on the surface and bulk properties of bituminous composites. UV exposure accelerates oxidative aging of bitumen, but its effects are concentrated mostly at the surface of the bitumen. Here, we examine morphology and chemical composition of the surfaces of non-aged thin films of bitumen and UV-aged thin films of bitumen using combined atomic force microscopy (AFM) and photothermal infrared (AFM−IR) spectroscopy; we further compare the findings with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…A complete characterization of surface phases is only possible with the combination of different techniques: (a) Fluorescence microscopy studies have shown fluorescent centres which were attributed to aromatics and resin fractions 34 . (b) AFM-IR observed the same centres and recorded sulfoxide stretching mode of organic sulfate esters at 1080 cm −1 and carbonyl stretching of ketones at 1700 cm −1 for the para-phase 38 . (c) ToF–SIMS measurements found chemical heterogeneities on the surface, however, the typical microstructural features occurring on bitumen surface, catana, peri and para phase, could not be resolved by means of the main molecular components aromatics, saturates, resins and asphaltenes 15 .…”
Section: Introductionmentioning
confidence: 70%
“…A complete characterization of surface phases is only possible with the combination of different techniques: (a) Fluorescence microscopy studies have shown fluorescent centres which were attributed to aromatics and resin fractions 34 . (b) AFM-IR observed the same centres and recorded sulfoxide stretching mode of organic sulfate esters at 1080 cm −1 and carbonyl stretching of ketones at 1700 cm −1 for the para-phase 38 . (c) ToF–SIMS measurements found chemical heterogeneities on the surface, however, the typical microstructural features occurring on bitumen surface, catana, peri and para phase, could not be resolved by means of the main molecular components aromatics, saturates, resins and asphaltenes 15 .…”
Section: Introductionmentioning
confidence: 70%
“…The morphology of flexible building tiles was further investigated by SEM. 37 To prove the enhanced compatibility by adding the WPAs, commercial emulsions (Shanghai Bao Li Jia Chemical Co., Ltd) were used as the control group. As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pure elemental sulfur is stable under UV irradiation, but it has been shown to be a weak photocatalyst, capable of splitting water into reactive radicals . Although the penetration depth of UV light into bitumen is shallow, the physical and chemical effects at the surface can be extreme. Even without added sulfur, oxidized sulfate (SO 4 ) minerals are a large proportion of the nonvolatile residue left behind after UV degradation of bitumen thin films …”
Section: Introductionmentioning
confidence: 99%